Beberapa Jejak Kelisanan dalam Novel di Kaki Bukit Cibalak Karya Ahmad Tohari: Perspektif Walter J. Ong - Bakti Sutopo (Jurnal Penelitian Pendidikan, 2011)
The aim of this study is to uncover the existence of the oral elements in the novelDi Kaki Bukit Cibalak by Ahmad Tohari. It is necessary to construct the convention of oraltheories that propounded by Walter J. Ong. This convention shows that there are severaloral elements in the novel. The oral element in the novel Di Kaki Bukit Cibalak there areagonistic, homeostatic, conservative, copious, episodic, additive, and moral teachings.